The therapeutic mechanism of Shenyuan Gan in lipopolysaccharide-induced neuroinflammation in BV2 microglial cells - Peng Sha; Peng Zhuang; Hu Qin; Liu Xinmin; Chen Ying; Shi Zhe (Digital Chinese Medicine, 2022)
Objective: To study the therapeutic effects of Shenyuan Gan (参远苷, SYG) on the inflammatory response in BV2 microglial cells induced by lipopolysaccharide (LPS). Methods: The cytotoxicity of SYG to BV2 microglial cells was evaluated using a Cell Counting Kit-8 (CCK-8) assay, and the effect of SYG concentrations on LPS-induced BV2 microglial cells was studied. The morphological changes were observed using an optical microscope. The nitric oxide (NO) concentration in cell culture supernatant was determined using Griess reagent. The expression of cytokines and inﬂammatory mediators were also measured by an enzyme-linked immunosorbent assay (ELISA). Western blot analysis was used to determine the levels of inducible NO synthase (iNOS), nuclear factor-kappa B (NF-κB) p65, alpha inhibitor of NF-κB (IκB-α), phosphorylation-IκB-α (p-IκB-α), NOD-like receptor 3 (NLRP3), and caspase-1 expression. Moreover, the expression of iNOS, NLRP3, and ionized calcium binding adapter molecule 1 (Iba1) was also observed using immunofluorescent staining. Results: SYG had a low cytotoxic effect on BV2 microglial cells and could significantly decr-ease LPS-induced morphological changes of BV2 microglial cells (P < 0.05). ELISA results showed that SYG significantly inhibited the LPS-induced increase in interleukin (IL)-1β and IL-6 in BV2 microglia cells (P < 0.05), and Western blot analysis showed that the phosphorylation levels of iNOS, NF-κB p65, and IκB-α as well as NLRP3 and caspase-1 expression were also significantly decreased, and IκB-α expression was increased after SYG treatment (P < 0.05, compared with the LPS-treated group). The immunofluorescence results were consistent with the Western blot results, and Iba1 staining indicated that the cell morphology tended to be resting. These results indicate that SYG has a certain inhibitory effect on LPS-induced inflammation in BV2 microglial cells. Conclusion: SYG can inhibit LPS-induced release of inflammatory factors in BV2 microglial cells by affecting the phosphorylation levels of NF-κB p65 and IκB-α. SYG is a valuable candidate for treating neuroinflammation-related diseases.